Thermal Stability Design of Asymmetric Support Structure for an Off-Axis Space Camera - Weiyang Song (Applied Sciences, 2021)
With the development of space optical remote sensing technology, especially off-axis space cameras, the thermal dimensional stability of the support structure has become increasingly demanding. However, the asymmetry of the camera structure has not been fully considered in the past design of the thermal stability of off-axis cameras. In order to solve this problem, a support structure with very low thermal deformation in the asymmetric direction is presented in this paper for an off-axis TMA camera. By means of the negative axial thermal expansion coefficient of carbon-fiber-reinforced plastics (CFRP), a composite laminate with near zero-expansion was obtained by adjusting the direction of fiber laying, and the asymmetric feature of the off-axis remote sensing camera structure was fully considered, thus enabling the support structure to have good thermal dimensional stability. We carried out a thermal load analysis and an optical analysis of the whole camera in the case of a temperature rise of 5 °C. The results show that the zero-expansion support structure has good thermal stability, and the thermal deformation in the asymmetric direction of the camera is obviously smaller than that of the isotropic laminate support structure. Compared with the isotropic support structure, the influence of thermal deformation on MTF is reduced from 10.43% to 2.61%. This study innovatively incorporates the asymmetry of the structure into the thermal sta-bility design of an off-axis TMA camera and provides a reference for the thermal stability design of other off-axis space cameras.